English Vocabulary Acquisition through MMORPGs: A Case Study of Ragnarok M Players - Siti Aisyah; Abdullah Azzam; Yudy Prasetyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Vocabulary acquisition plays a central role in English language learning, yet many learners struggle to expand their vocabulary through conventional classroom instruction. Recent developments in digital technology have introduced alternative platforms for language acquisition, including Massively Multiplayer Online Role-Playing Games (MMORPGs), which offer rich linguistic input and interactive environments. This study investigates how Indonesian EFL learners acquire English vocabulary through their engagement with Ragnarok M: Eternal Love, a popular MMORPG. Employing a descriptive qualitative research design, data were collected from 50 active players via an online questionnaire consisting of both closed- and open-ended items. The findings reveal that vocabulary is acquired incidentally through repeated exposure to in-game texts such as quest instructions, NPC dialogues, item descriptions, and player communication. Players employed various strategies for vocabulary learning, including contextual guessing, translation tools, and peer support. Social interaction, motivation, and gameplay immersion were identified as significant factors influencing vocabulary retention. These results support theoretical perspectives such as Krashen’s Input Hypothesis, Vygotsky’s Sociocultural Theory, and Gee’s Situated Learning. The study highlights the potential of MMORPGs as informal learning environments and provides pedagogical implications for integrating game-based learning into English language instruction. Keywords: A MMORPG, Game-Based Learning, Informal Learning, Ragnarok M, Vocabulary Acquisition.